Persuasive effect of narrative and statistical evidence combinations - Good, Chelsea (Kansas State University, 2010)
This study examines the effect of using a combination of narrative and statistical evidence on persuasion. Literature is divided on whether narrative or statistical evidence is more persuasive. There are a number of explanations to support both arguments, but arguing that one is superior may be flawed because these evidence types function differently and are not necessarily competitive. A few studies support the use of both narratives and statistics together, but none of these studies address the proportions when combining the two evidence types. This study fills the gap by creating messages with different degrees of anecdotal and statistical evidence. Conditions range from full anecdotal support to full statistical support and include three blended conditions (25/75, 50/50, 75/25). A total of 384 participants were surveyed via a national survey company. Results indicate that evidence type (narratives or statistics) and the various blends of evidence type do not change the persuasive effectiveness of a claim. While supporting persuasive claims with some kind of evidence is imperative, general populations do not favor one evidence type (narratives or statistics) over the other, and in fact, may be split in what they find more effective. Nor do people believe that evidence types function all that differently—at least when it comes to the support they provide for claims from livestock producers. Results, implications and recommendations for future research are discussed in detail.
Keywords: Persuasion; Narratives; Statistics; Evidence type; Blending evidence; Agricultural communications; Speech Communication (0459)